Answer:
Explanation:
1)a ) Let the constant proportionality =k
Direct proportion.So, y = kx
Plugin y = 6 and x =2 and find k
6 = k*2
6/2 = k
k = 3
Constant proportionality = 3
b) y = 3x
When x = 7 ; y = 3*7 = 21
y = 21
c)When x = 9,
y = 3*9
y = 27
d) When y = 9,
9 = 3*x
9/3 = x
x = 3
e)when y = 30
30 = 3*x
30/3 =x
x = 10
3) y is inversely proportion to x³
![y =k(1)/(x^(3))\\\\3 =k *(1)/(2^(3))\\\\3=k*(1)/(8)\\\\3*8=k\\\\24 = k](https://img.qammunity.org/2023/formulas/mathematics/college/enh12csen3rr0yp3y0m5fjplzjowcyermp.png)
b) when x = 4
![y=24*(1)/(4*4*4)\\\\y=(3)/(8)](https://img.qammunity.org/2023/formulas/mathematics/college/cm5mpfql0rgi1q8rhnjve1dyjpuag4o16h.png)
c) When x = 6
![y = 24*(1)/(6*6*6)\\\\y=(1)/(9)](https://img.qammunity.org/2023/formulas/mathematics/college/pj5cnl31vt72cwbzippnrsn9ch3a3jjzmc.png)
d) When y = 24
![24= 24*(1)/(x^(3))\\\\x^(3)*24=24\\\\x^(3)=(24)/(24)\\\\x^(3)=1\\\\x = 1](https://img.qammunity.org/2023/formulas/mathematics/college/4zj14klkuggopq255gntrgoy1k1pne2i4t.png)